Studi kasus pasteurellosis and nematodiasis pada babi di laboratorium Patologi Fakultas Kedokteran Hewan Universitas Gadjah Mada - Purwandari K., Yuli (Fakultas Kedokteran Hewan Institut Pertanian Bogor, 2010)
Evidence of infection with Pasteurella sp.was observed at necropsy of twenty pigs, that were examined during July, 2007 until July, 2008 in Departement of Pathology, Faculty of Veterinary Medicine, Gadjah Mada University , Yogyakarta, Indonesia. Severe disease were observed as the principal cause of mortality in the pigs. Fifthy five percent occurred Pasteurella infection, thirthy percent occurred Parasitic infection and the other occurred pneumonia, thrichuris and coccidia infection. Characteristic necropsy lesion included a marble area, congestive and hard consistency on lung. Intestinal lesions included hemorrhagic on mucosa of the small intestine by A. suum and T. Suis. And the microscopic changes included pleuritis which infiltrate neutrofil, makrofag and hemorrhagi, interstitial pneumonic and and bronchopneumonic on lung.